207 An atypical cause of longitudinally extensive transverse myelitis after an allogeneic haemopoietic stem cell transplant. Issue 12 (14th November 2019) - Kemp, Michael; Keh, Yann Shern; Dayanandan, Rejith; Saif, Muhammad; Nixon, John
Abstract : We present an unusual case of longitudinally extensive transverse myelitis (TM) with atypical features following allogeneic stem cell transplant. A 53 year old male with a history of allogeneic stem cell transplant (SCT) two years earlier for myelofibrosis presented with a two day history of difficulty walking. Clinically he had a left Brown-Sequard syndrome. MRI showed a cord lesion preponderant to the left anterior quadrant at T7-9. Initially independently mobile he rapidly deteriorated over two days, a week following admission, developing a dense flaccid paraparesis with a sensory level to the costal margin. Repeat imaging showed diffuse cord signal change from C6 downwards. In addition a persistent fever and rash emerged. Treated with high dose steroids and plasma exchange, the clinical course has progressed no further and rehabilitation continues however imaging has shown significant improvement. Whilst there are case reports of TM after allogeneic SCT, they've typically responded quickly to immunosuppressive treatment which we have not yet seen. There was no active graft versus host disease at the time of presentation which makes this to be an unlikely cause of this presentation. This case highlights the lack of detailed cases and imaging of similar reported presentations.